Effects of ecological restoration projects on changes in land cover: A case study on the Loess Plateau in China - Zhao, Jun (Sci Rep, 2017)
Changes in land cover have become key components of global environmental change and represent the impact of human activity. To better understand the fundamental processes of land transition characteristics before and after the implementation of ecological programmes, we determined the dominant systematic changes in land cover in Yongshou, a hilly-gully region on the Loess Plateau. This was achieved by performing an in-depth analysis of a cross-tabulation matrix and a modified spatial dynamic degree model. Our results indicated that (1) forest land and cultivated land were the most important land cover types in Yongshou and their persistence would greatly affect the landscape pattern of the entire region; (2) the most significant changing signals in the study area during the periods 1992–2000 and 2000–2013 were from immature forest land to forest land, cultivated land to orchards and orchards to construction land; and (3) the region that experienced the most changes during 1992–2000 was the densely populated county seat of Yongshou; however, from 2000–2013, the region of most changes was Changning, a town located in the northcentral region of Yongshou. These findings reveal the main characteristics of the land cover changes in this region and provide insight into the processes underlying these changes.